Research on design method of metamaterial sound field control barrier based on transformer vibration and noise - Xinzhe Zhao; Zhibin Shuai; Yifeng Zhang; Zijian Liu (Energy Reports, 2022)
In order to analyze the propagation path of vibration noise, and carry out finite element numerical calculation research based on electro-magnetic–solid-acoustic multiphysics coupling, a single-phase two-column dry-type transformer is used as the noise source in this paper. According to the distribution characteristics of the spatial sound field and the vibration noise amplitude–frequency characteristics of the transformer, a topology design method of the space coiled acoustic metamaterial (SCAMM) unit is proposed and the analytical calculation methods of acoustic parameters such as sound pressure reflection/transmission coefficient of various SCAMM units are deduced. Besides, the effects of parameters such as the longitudinal width a, the waveguide width b, the ratio of waveguide width to longitudinal width b/aand transverse width t on the SCAMM unit sound transmission loss (STL) are studied, and the anti-resonance frequencies are adjusted by parameter optimization method to achieve the optimal sound insulation effect. In the end, the sound field control barrier based on the SCAMM for transformer vibration and noise suppression is designed, and relevant experiments are carried out. The experiments show that the sound field control barrier based on the SCAMM can reduce the transformer noise sound pressure level (SPL) of the main noise frequencies by up to 25 dB with a thickness of only 4 cm and ventilation.